Application of the Attitude Toward Enterprise (ATE) test on scondary school learners in South Africa - Stephan P van der Merwe; Andre G Steenekamp; Rosemary Athayde (South African Journal of Economic and Management Sciences, 2011)
The main aim of this research paper was to discuss the application of the Attitude Toward Enterprise (ATE) Test1 developed by Kingston University, London on secondary school learners in South Africa. A total of 1 748 usable questionnaires were gathered from grade 10 learners in the Sedibeng District and utilised for statistical analysis. Five factors with eigen-values greater than one describing the entrepreneurial attitudes of young learners were extracted during exploratory factor analysis. Tests for reliability and construct correlation produced satisfactory results to recommend the Enterprise Attitude Questionnaire for further use on young learners in South Africa. A comparison of the mean differences between the constructs for demographic variables produced statistically significant differences in a number of instances, but no visible effects or practical significance to suggest that these differences have any effect in practice. Practical recommendations are offered for further employment of the Enterprise Attitude Questionnaire in entrepreneurship research on young learners.